THE EFFECT OF PROJECT-BASED LEARNING TOWARDS SCIENCE LITERATION OF ELEMENTARY SCHOOL STUDENTS - Anna Roosyanti (JURNAL PENA SAINS, 2020)
This research aims to investigate the effects of Project-Based Learning towards Science Literation of Elementary School Students. Students on fifth-A grade and fifth-B grade Ma'arif Al-Fattah Elementary School Surabaya in the academic year 2018-2019 conducted this research, with fifth-A grade population as the control class and fifth-B grade population as the experimental class. This research is quantitative research with a Paired Sample T-test analysis, where the independent variable is Project-Based Learning and students' Science Literacy skills as a dependent variable. Data analysis shows that t arithmetic t table is 21,308 1,705, so rejected Ho and accepted Ha. Sig. (2-tailed) 0,000 0.05, so rejected Ho and accepted Ha. This research concludes that there is a significant effect of Project-Based Learning on elementary school students' scientific literacy skills.